2017
DOI: 10.12816/0042857
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitude of Basic Life Support among Medical Students at King Abdul-Aziz University

Abstract: Aim of the work: basic life support (BLS) refers to the skills that require few tools to save lives of the victims of cardiac or respiratory arrests. All healthcare providers are required to master these skills in order to maximize the care to those who experience such emergencies. This study aimed to assess the knowledge and attitude toward BLS in King Abdul-Aziz University among 3 rd to 6 th year medical students. Methods: this is a retrospective cross-sectional study conducted in King Abdul-Aziz University,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
1
3
1
Order By: Relevance
“…There was no significant association between age and gender with the attitude level towards BLS training in this study which showed that the importance of BLS training on the students despite of their age and gender. The findings on this study that showed a positive attitude among participants was also found to contradict with a previous study that reported a decrease in attitude towards BLS training among medical students in year 3, 4 and 5 in Saudi Arabia (25).…”
Section: Association Between Sociodemographic Characteristic and Know...contrasting
confidence: 99%
See 1 more Smart Citation
“…There was no significant association between age and gender with the attitude level towards BLS training in this study which showed that the importance of BLS training on the students despite of their age and gender. The findings on this study that showed a positive attitude among participants was also found to contradict with a previous study that reported a decrease in attitude towards BLS training among medical students in year 3, 4 and 5 in Saudi Arabia (25).…”
Section: Association Between Sociodemographic Characteristic and Know...contrasting
confidence: 99%
“…In previous study, female was reported to achieved higher score than male and third year dental students have higher mean knowledge scores than fifth year (14, 23). In another study, year 6 medical students scored the highest mean of total correct answers compared to year 3, 4 and 5 medical students (25).…”
Section: Association Between Sociodemographic Characteristic and Know...mentioning
confidence: 90%
“…For trained understudies, it was 6/15 (4/15-8/15) and for untrained understudies, it was 5/15 (3/15-7/15). Past CPR preparing had a critical impact on the right reactions (P<0.01), proving the study by Yousef, et al [11]. Out of 370 medical students who participated in this study, 41% had received BLS training more than once, while 59% had received only a mandatory BLS course during their second academic year.…”
Section: Discussionsupporting
confidence: 81%
“…We have not assessed the attitude of ambulance personnel towards BLS, unlike other studies that have captured the attitude of participants,[ 2 3 4 5 7 ] as we felt that all ambulance personnel should be skilled in providing BLS as and when needed and they should have a positive attitude towards BLS. The patients needing BLS lose a vital time during their transport from one center to another.…”
Section: Discussionmentioning
confidence: 99%
“…There is published data regarding the knowledge of BLS among the doctors, medical students, paramedical students, and school teachers. [ 1 2 3 4 5 6 7 ] But we do not have any published data regarding the BLS knowledge among the ambulance personnel. With this background, the primary objective was to study the level of knowledge on BLS among the ambulance personnel.…”
Section: Introductionmentioning
confidence: 99%